2004
DOI: 10.1016/j.cemconcomp.2004.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cement pastes and mortars by a combination of backscatter-based SEM image analysis and calculations based on the Powers model

Abstract: Formation of microstructure in cement pastes and mortars were quantitatively analyzed by the SEM-BSE image analysis. Effects of water/cement ratio and of the addition of mineral admixtures on the contents of unhydrated cement particles and pores were discussed. The proportions of each phase obtained by the analyses were compared with proportions calculated on the Powers model. It was found from comparisons that the volume fractions of the residual cement and pores obtained by the image analysis did not contrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(56 citation statements)
references
References 15 publications
(20 reference statements)
6
47
0
Order By: Relevance
“…Only the coarser porosity was 355 evaluated using this approach, as the finer porosity was invisible to the SEM. This suggests that the 356 coarse porosity dominates the compressive strength, independent of the mix designs, which is in 357 agreement with previous observations 44,70,71,72 . 358…”
Section: Discussionsupporting
confidence: 87%
“…Only the coarser porosity was 355 evaluated using this approach, as the finer porosity was invisible to the SEM. This suggests that the 356 coarse porosity dominates the compressive strength, independent of the mix designs, which is in 357 agreement with previous observations 44,70,71,72 . 358…”
Section: Discussionsupporting
confidence: 87%
“…4. The two quantities had a strong positive correlation (≈ 1), establishing that the BEI analysis is able to detect the microstructure of specimens as reported previously (Igarashi 2004;Scrivener 2004 …”
Section: Bei Analysissupporting
confidence: 80%
“…Unhydrated cement (UH), calcium hydroxide (CH), C-S-H (including fine pores and other hydrates), and pores larger than 0.32 µm (coarse porosity) were distinguished using image analysis software and setting brightness thresholds. The average area fraction of each phase was considered to be the volume fraction (Igarashi et al 2004).…”
Section: Backscattered Electron Image (Bei) Measurementsmentioning
confidence: 99%
“…The measurement of hydration degree was done by mean of the backscattered electron image (Igarashi et al 2004) as shown in Fig. 17.…”
Section: The Measurement Of Hydration Degreementioning
confidence: 99%